Evolution of Cataract Surgery in Pakistan over the Past Four Decades: Doi: 10.36351/pjo.v41i2.2019 - Malik, Abdul Majeed (Pakistan Journal of Ophthalmology, 2025)
Cataract is one of the leading causes of reversible blindness worldwide.1 In Pakistanreversible blindnessdue to cataract remains the leading cause due to increase in aging population, poverty and comparatively lesser surgical facilities.2The prevalence of cataract blindness was higher in women than men (1.80% versus 1.67%, p<0.001). The prevalence of cataract causing <6/60 in eyes was 5.0% (95% CI 4.7%, 5.2%), which projects to an estimated 3 560 000 eyes with a visual acuity of <6/60 caused by cataract in Pakistan (year 2003). This number was projected to increase to 7380 000 by the year 2020.3